Penelitian Bahan Pencerah dan Pelembab Kulit dari Tanaman Indonesia - Wih, Wong Lip; Ranti, Anna S; Wasitaatmadja, S M; Suryaningsih, Suryaningsih; Junardy, F D; Maily, Maily (UI Scholars Hub, 2009)
The market of skin lightening product grows very fast. This is especially true in almost all Asian countries. Martha Tilaar Innovation Center has found natural ingredients which function as anti oxidant and anti tyrosinase in vitro. These ingre-dients are extracted from Indonesian plants namely Lansium domesticum (LE)*) and Phyllantus niruri (PE) *). Several aspects should be considered to utilize these ingredients in cosmetic, such as, the stability of the plant materials and their safety and efficacy on human skin. The objective of this research is to study whether these ingredients in cosmetic preparations have skin lightening and skin moisturizing effects clinically. This article will describe the safety and efficacy evaluation on natu-ral ingredients extracted with ethanol from the above Indonesian plants. The safety evaluation is conducted clinically using Repeated Opened Patch Test (ROPT) and followed by Single Closed Patch Test (SCPT) in more than 50 selected healthy volun-teers. Their irritation properties on mucous membrane were evaluated using HETCAM method. Then, their efficacies on lightening and moisturizing were conducted in more than 26 volunteers, using Mexameter MX 16 and Corneometer CM 820. These results revealed that both extracts are safe on human skin and mucous membrane and can function as skin lightening agent. Lansium domesticum extract also has skin moisturizing effect.